Analysis of the factors causing tidal flooding in Penjaringan District, North Jakarta (Muara Angke, Muara Karang, Muara Baru) - Arfilian Permana Putra; Raafi Widyaputra Yulianyahya; Debby Syafriyandi; Ansadilla Niar Sitanggang; Christian Dwi Putra Widjaya; Rosdiana Trialita; Ryan Maulana; Adam Wisnu Saputra; Athallah Adhika Pradhana Purnomo; Fina Amelia (Pengmasku, 2026)
Tidal flooding is not only caused by seawater intrusion but also reflects the complexity of urban environmental problems. Contributing factors include land subsidence due to excessive groundwater extraction, inadequate drainage systems, degradation of mangrove ecosystems, and land-use changes resulting from coastal reclamation. Therefore, this study examines the recurring phenomenon of tidal flooding in the coastal areas of Penjaringan District, North Jakarta, particularly in Muara Angke, Muara Karang, and Muara Baru. This study employs a mixed-methods approach through direct field observations, in-depth interviews with residents and community leaders, and the distribution of questionnaires to 100 respondents in the affected areas. The results indicate that tidal flooding has significant impacts on the economic, social, and health aspects of the community. Daily activities are disrupted, household incomes decline, and the risk of disease increases due to poor sanitation conditions during flood events. Although communities have implemented various adaptation measures, most respondents perceive that government interventions have not been effective or equitable. This study emphasizes the importance of collaboration between the government and local communities in developing water control infrastructure, rehabilitating mangrove ecosystems, improving drainage systems, and providing education and economic assistance to enhance the resilience of coastal communities to tidal flooding.